Towards cleaner desalination systems utilizing waste heat: A bibliometric analysis - Maryam Nooman AlMallahi; Sara Maen Asaad; Mahmoud Elgendi (International Journal of Thermofluids)
Water scarcity is a global issue facing the coming generations. Desalination is a dependable, nonconventional freshwater production method. However, desalination is an energy-intensive water treatment method. The primary energy source used to power various desalination processes for thermal and electrical energy consumption is fossil fuels, such as coal, oil, and gas. The widespread use of fossil fuels has been linked to climate change and global warming, leading to numerous demands to reduce their usage and energy utilization. Waste heat has an excellent potential for energy recovery that can reduce the consumption of fossil fuels. This research study has been conducted to evaluate related waste heat desalination literature with data analysis, bibliometric, and clustering methods. Based on articles published between 2013 and 2023, the current study analyzed existing trends, distribution of publication subjects, journals' performances, countries' collaborations, affiliations' performances, most cited publications, authors' contributions, keyword analysis, and future perspectives on waste heat desalination systems. The findings showed that the most active journal in this field is Desalination, with 133 publications and 6332 citations. China led in publications with 242, while the United States topped the list of citations with 3598. Also, King Abdullah University of Science and Technology in Saudi Arabia published 50 documents. The top 10 institutions in this field of research are in the Middle East and North Africa (MENA) region and Asia, particularly in Saudi Arabia, China, Iran, Egypt, and Singapore. Moreover, the most frequently used terms are analyzed and clustered into three main topics. The top 3 clusters are solar-powered desalination technologies, membrane-powered desalination technologies, and power cycles driving desalination technologies.